FYR Macedonia Gender Diagnostic : Gaps in Endowments, Access to Economic Opportunities and Agency - World Bank (Washington, DC, 2013)
Former Yugoslav Republic (FYR) of Macedonia has closed several gaps in gender inequalities, particularly in education and health, but key disparities persist in access to economic opportunities and agency, particularly among certain ethnic groups. This report provides an overview of gender disparities in several outcomes related to human and physical endowments, access to economic opportunities, and agency. In addition, it offers potential explanations of these gaps and, in the process, identifies knowledge gaps to be addressed in future research. On average, FYR Macedonia has achieved gender equality in health and in education; however, gender disparities persist for certain population subgroups. However, women are more likely than men to choose general programs or social sciences as their primary field of education. Both men and women are unlikely to undertake additional training following their initial education, but each for different reasons: women are more likely than men to cite family obligations as a key factor in this decision (19 percent of women compared to 1.5 percent of men) as women devote a much larger percentage of their time to domestic activities. In addition, only a limited number of children enroll in pre-school. Female labor force participation is low, particularly among women who have received only a primary education or less. Although female-managed businesses are as productive as male-managed businesses, few women are entrepreneurs. Women's participation in collective actions is limited, and gender stereotypes remain pervasive. Looking forward, further efforts to increase women's access to economic opportunities in FYR Macedonia are needed. Policies aimed at fostering the competitiveness of the private sector for job creation is a key for addressing the high unemployment rates faced by both men and women. In the case of FYR Macedonia, policies can also increase female labor force participation by affecting the potential wages or the reservation wages of less skilled women.